Feasibility of a pulmonary rehabilitation programme for patients with symptomatic chronic obstructive pulmonary disease in Georgia: a single-site, randomised controlled trial from the Breathe Well Group. Issue 9 (23rd September 2022) - Maglakelidze, Mariam; Kurua, Ia; Maglakelidze, Nino; Maglakelidze, Tamaz; Chkhaidze, Ivane; Gogvadze, Ketevan; Chkhaidze, Natia; Beadle, Helen; Redden-Rowley, Kelly; Adab, Peymane; Adams, Rachel; Chi, Chunhua; et al.
Abstract : Objectives: To assess the feasibility of delivering a culturally tailored pulmonary rehabilitation (PR) programme and conducting a definitive randomised controlled trial (RCT). Design: A two-arm, randomised feasibility trial with a mixed-methods process evaluation. Setting: Secondary care setting in Georgia, Europe. Participants: People with symptomatic spirometry-confirmed chronic obstructive pulmonary disease recruited from primary and secondary care. Interventions: Participants were randomised in a 1:1 ratio to a control group or intervention comprising 16 twice-weekly group PR sessions tailored to the Georgian setting. Primary and secondary outcome measures: Feasibility of the intervention and RCT were assessed according to: study recruitment, consent and follow-up, intervention fidelity, adherence and acceptability, using questionnaires and measurements at baseline, programme end and 6 months, and through qualitative interviews. Results: The study recruited 60 participants (as planned): 54 (90%) were male, 10 (17%) had a forced expiratory volume in 1 second of ≤50% predicted. The mean MRC Dyspnoea Score was 3.3 (SD 0.5), and mean St George's Respiratory Questionnaire (SGRQ) 50.9 (SD 17.6). The rehabilitation specialists delivered the PR with fidelity. Thirteen (43.0%) participants attended at least 75% of the 16 planned sessions. Participants and rehabilitation specialists in the qualitative interviews reported that the programme was acceptable, but dropout rates were high in participants who lived outside Tbilisi and had to travel large distances. Outcome data were collected on 63.3% participants at 8 weeks and 88.0% participants at 6 months. Mean change in SGRQ total was −24.9 (95% CI −40.3 to –9.6) at programme end and −4.4 (95% CI −12.3 to 3.4) at 6 months follow-up for the intervention group and −0.5 (95% CI −8.1 to 7.0) and −8.1 (95% CI −16.5 to 0.3) for the usual care group at programme end and 6 months, respectively. Conclusions: It was feasible to deliver the tailored PR intervention. Approaches to improve uptake and adherence warrant further research. Trial registration number: ISRCTN16184185 .